IDENTIFIKASI KESEHATAN BIBIT BALANGERAN (Shorea Balangeran K) DI PERSEMAIAN Health Identification of Balangeran (Shorea Balangeran K) seeds in nursery - Susilawati Susilawati; Dina Naemah (Jurnal Hutan Tropis, 2018)
Balangeran (Shorea balangeran Korth.) is a genuine type of peat swamp plant that has rapid growth so it has the potential to be developed in the framework of peat swamp forest development. The success of planting can not be separated from the provision of good quality seeds in the nursery. Pests and diseases are one of the critical success factors in the cultivation of this plants. This study aims to identify the causes and types of damage that attacked balangeran seedlings, analyzing pest and disease attacks on balangeran seedlings.The object of this research is balangeran seedlings that come from seed (generative) which has 6 months old in nursery Tumbang Nusa Central Kalimantan. The data were obtained through field observation by observing the sample of balangeran seed.The next data are processed according to standards and criteria of crop research results based on  the standards and the codes of the Environmental Monitoring and Assessment Program (EMAP). Based on the result of the research,  from 220 seed balangeran that was observed 164 seeds (74,24%) are sick and 56 seeds (25,45%) are  healthy. The intensity of total attack is about 74,54%,  the intensity of pest attack is about  42,27% and disease attack intensity is 39,54% with highest attack severity 20-29%.Keywords: Enviromental Monitoring and Assessment; the health of the seed; BalangeranBalangeran (Shorea balangeran Korth./Burck) merupakan jenis asli tanaman rawa gambut yang memiliki pertumbuhan cepat sehingga memiliki potensi untuk dikembangkan dalam rangka pembangunan hutan rawa gambut. Keberhasilan penanaman tidak terlepas dari pengadaan bibit berkualitas baik di persemaian. Hama dan penyakit tanaman merupakan salah satu faktor penentu keberhasilan dalam budidaya tanaman. Penelitian ini bertujuan untuk mengidentifikasi penyebab dan tipe kerusakan yang menyerang bibit balangeran, menganalisis serangan hama dan penyakit pada bibit balangeran. Objek penelitian ini adalah bibit balangeran yang berasal dari biji (generatif) yang telah berumur 6 bulan di persemaian Tumbang Nusa Kalimantan Tengah.Data diperoleh melalui observasi di lapangan dengan mengamati setiap bibit balangeran yang dijadikan sampel. Data selanjutnya diolah berdasarkan standar dan kriteriahasil penelitian tanaman menurut standar dan kodefikasi bukuEnvironmental MonitoringandAssessmentProgram (EMAP). Berdasarkan hasil penelitian yang diperoleh menunjukkan dari 220 bibit balangeran yang diamati 164 bibit (74,24%) sakit dan 56 bibit (25,45%) sehat. Intensitas serangan keseluruhan sebanyak 74,54%, Intensitas serangan hama sebanyak 42,27% dan intensitas serangan penyakit sebanyak 39,54% dengan tingkat keparahan serangan tertinggi 20-29%.Kata Kunci:Monitor dan Penilaian Lingkungan; Kesehatan bibit;Balangeran